4(3n-2)=(7n+4)+6

Simple and best practice solution for 4(3n-2)=(7n+4)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3n-2)=(7n+4)+6 equation:


Simplifying
4(3n + -2) = (7n + 4) + 6

Reorder the terms:
4(-2 + 3n) = (7n + 4) + 6
(-2 * 4 + 3n * 4) = (7n + 4) + 6
(-8 + 12n) = (7n + 4) + 6

Reorder the terms:
-8 + 12n = (4 + 7n) + 6

Remove parenthesis around (4 + 7n)
-8 + 12n = 4 + 7n + 6

Reorder the terms:
-8 + 12n = 4 + 6 + 7n

Combine like terms: 4 + 6 = 10
-8 + 12n = 10 + 7n

Solving
-8 + 12n = 10 + 7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-7n' to each side of the equation.
-8 + 12n + -7n = 10 + 7n + -7n

Combine like terms: 12n + -7n = 5n
-8 + 5n = 10 + 7n + -7n

Combine like terms: 7n + -7n = 0
-8 + 5n = 10 + 0
-8 + 5n = 10

Add '8' to each side of the equation.
-8 + 8 + 5n = 10 + 8

Combine like terms: -8 + 8 = 0
0 + 5n = 10 + 8
5n = 10 + 8

Combine like terms: 10 + 8 = 18
5n = 18

Divide each side by '5'.
n = 3.6

Simplifying
n = 3.6

See similar equations:

| 45+3x+r=180 | | -.014x^2+.68x=0 | | 3x+23=52 | | 2(3x-1)+9=4x+15 | | A+bxc= | | 2x-3*2=x-9 | | 3x-124-12x=128 | | -4x+10=2y | | 2x-3+2x-3=x+9 | | 11x+19=41 | | 5x^6+x^4+5x^2+7x-65=0 | | -7k+3-6k=-35 | | 6x-4=7(x-8) | | y(2-y)=6-[y(y)+3y-4] | | 13=0.7x+2.50 | | x^2-120x=-2780 | | 3x+8y=-16 | | tanx=2.0417 | | 4(r+1.4)-6r=7.3 | | -5x-8y=59 | | 3a+b=5c | | 5x^2-7y^2=0 | | -4(-12+k)=-12 | | 2x^2+6x-6x-7+3=0 | | -16-3x=40-5x | | 5u(u+9)(u-6)=0 | | 6z-4z+2z= | | 6(u+2)=48 | | (-x-6)-(2x+5)= | | x+12+9x=40 | | X^3-2(2+6)=0 | | 3(n-3)=-42 |

Equations solver categories